Direct embeddings of relatively hyperbolic groups with optimal ℓp compression exponent - Hume, D (De Gruyter, 2015)
We prove that for all p > 1, every relatively hyperbolic group has ` p compression exponent equal to the minimum of the exponents of its maximal peripheral subgroups. This improves results of Dadarlat–Guentner and Dreesen. As a first step we give a direct geometric proof that hyperbolic groups have ` p compression exponent 1, independent of those given by Bonk–Schramm, Buyalo–Dranishnikov–Schroeder, Gal and Tessera.